The prevalence of urinary incontinence among women in Oman - Al Busaidi, Kauthar Sulaiman Ahmed (Curtin University, 2011)
This thesis describes an investigation of the prevalence of urinary incontinence (UI) among Omani women. First, a culturally specific questionnaire for interviews in English or Arabic was developed and tested. Next, feasibility of sampling and data collection methods were field-tested in 120 urban women. Finally, a national population-based sample of 800 women was interviewed. The prevalence of UI was 42.9%. Although UI was bothersome to 65%, care seeking was low (23.3%).